Implementasi Zahir Accounting Versi 6.0 Pada Toko Karya Sejati Tasikmalaya - Zakia, Ade Ucu Tri; Widiastuti, Lisda; Wasiyanti , Sri; Lisda (LPPM Universitas Bina Sarana Informatika, 2024)
Toko Karya Sejati (KS) is a trading company. Currently, there is no specific system or application in place, making the accounting data processing inefficient, as it is still recorded manually. This manual recording makes the data susceptible to damage or loss and requires a significant amount of time to generate reports. The objective of this research is to determine the operating system, design the system, analyze and test it, and perform accounting data processing. This study is beneficial in establishing accounting data processing at Toko Karya Sejati (KS). The research method employed is qualitative, involving interviews with KS business managers directly handling financial data processing issues, as well as direct observation of the existing system. The Zahir accounting system version 6.0 is proposed as a solution to the arising issues. With Zahir version 6.0, accounting data processing from transaction recording to financial report generation is much more accurate and efficient compared to manual systems.